1995
DOI: 10.1016/0014-5793(95)01380-6
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic classification of the major superfamily of membrane transport facilitators, as deduced from yeast genome sequencing

Abstract: From the approximately 5000 open reading frames presently identified by systematic sequencing of the yeast genome, 100 Saccharomyces cerevisiae transport proteins belonging to the major facilitator superfamily (MFS), were assigned to 17 families on the basis of extensive database searches and binary comparisons. These families include multidrug resistance proteins and transport proteins for sugars, amino acids, uracil/ aliantoin, allantoate, phosphate, purine/cytosine, proteins, peptides, potassium, sulfate, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0
1

Year Published

1997
1997
1998
1998

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 14 publications
(17 reference statements)
4
63
0
1
Order By: Relevance
“…which were proposed to be integral membrane proteins and conducive to resistance phenotypes when present in multicopies (40 -43). These proteins belong to either the ABC (ATPbinding cassette) family or the MFS (major facilitator superfamily) family (43)(44)(45). The putative Acr3p, lacking ATPbinding cassette, may belong to the MFS superfamily.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…which were proposed to be integral membrane proteins and conducive to resistance phenotypes when present in multicopies (40 -43). These proteins belong to either the ABC (ATPbinding cassette) family or the MFS (major facilitator superfamily) family (43)(44)(45). The putative Acr3p, lacking ATPbinding cassette, may belong to the MFS superfamily.…”
Section: Discussionmentioning
confidence: 99%
“…The putative Acr3p, lacking ATPbinding cassette, may belong to the MFS superfamily. However, the Acr3p is not present in the group of 100 S. cerevisiae transport proteins classified as the MFS proteins (43)(44)(45). MFS proteins comprise 500 -600 amino acids with 12 transmembrane helices and share sequence similarities suggesting the common ancestral origin (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining S2 permease (UNK1) has not yet been identified genetically. However, as structurally related amino acids often have structurally related permeases (see basic amino acid permease cluster II: Nelissen et al, 1995), it is quite probable that the other branched-chain amino acid permease is encoded by PAP1 (yeast genomic clone YD9609.02) which is the permease identified as most homologous to BAP2 by sequence analysis (Nelissen et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…There are currently 16 permeases classified in the major family of amino acid permeases in Saccharomyces cerevisiae (André, 1995). Many of these have been identified previously through mutant studies and their substrate specificity is known; others are open reading frames, identified in the Yeast Genome Project as homologous to other members of the family (Nelissen et al, 1995). The known amino acid permeases show several common features: a length of approximately 600 amino acids, a central hydrophobic section which contains 12 putative membrane-spanning domains, no N-terminal signal sequence and a C-terminal which is fairly hydrophilic and may be involved in permease regulation (Grausland et al, 1995;Zhu et al, 1996).…”
Section: Introductionmentioning
confidence: 99%